2023
DOI: 10.1021/acs.jmedchem.2c01630
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Cytotoxicity with Lego-like Chemistry: Upgrading Mitochondriotropic Antioxidants with Prototypical Cationic Carrier Bricks

Abstract: Although the lipophilic triphenylphosphonium (TPP + ) cation is widely used to target antioxidants to mitochondria, TPP +based derivatives have shown cytotoxicity in several biological in vitro models. We confirmed that Mito.TPP is cytotoxic to both human neuronal (SH-SY5Y) and hepatic (HepG2) cells, decreasing intracellular adenosine triphosphate (ATP) levels, leading to mitochondrial membrane depolarization and reduced mitochondrial mass after 24 h. We surpassed this concern using nitrogen-derived cationic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In this study, we observed mitochondrial membrane depolarization in the gastrocnemius of Dityr-treated mice, which suggested that the integrity of the mitochondrial membrane structure was damaged by Dityr. Numerous studies have affirmed the connection between membrane depolarization and ATP generation . When coupled with the preceding experimental outcomes, it is substantiated that Dityr exposure may induce mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, we observed mitochondrial membrane depolarization in the gastrocnemius of Dityr-treated mice, which suggested that the integrity of the mitochondrial membrane structure was damaged by Dityr. Numerous studies have affirmed the connection between membrane depolarization and ATP generation . When coupled with the preceding experimental outcomes, it is substantiated that Dityr exposure may induce mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous studies have affirmed the connection between membrane depolarization and ATP generation. 51 When coupled with the preceding experimental outcomes, it is substantiated that Dityr exposure may induce mitochondrial dysfunction. Furthermore, the current investigation has demonstrated the detrimental impact of Dityr treatment on various pivotal processes implicated in the regulation of mitochondrial function within the gastrocnemius muscle of mice.…”
Section: Discussionmentioning
confidence: 97%
“…The data revealed that only compound 2e exhibited no detrimental effects on cellular health, as indicated by a 90.88% NR uptake. This highlights the significance of replacing the TPP cation with alternative nitrogen-based carriers to reduce inherent toxicity [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chromatographic hydrophobicity index (CHI) values at pH 2.3 were determined using an experimental protocol described elsewhere . The acidic conditions used were relevant to prevent ionization of the phenolic function and to avoid peak tailing.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…The chromatographic hydrophobicity index (CHI) values at pH 2.3 were determined using an experimental protocol described elsewhere. 12 The acidic conditions used were relevant to prevent ionization of the phenolic function and Statistical Analysis. For each assay, all experiments were performed in triplicate and the coefficient of variation was always <10%.…”
mentioning
confidence: 99%